2018
DOI: 10.1002/jwmg.21481
|View full text |Cite
|
Sign up to set email alerts
|

Activity of an endangered bat increases immediately following prescribed fire

Abstract: Spatiotemporal responses of bats to fire are not well understood. Fire can indirectly influence bat activity through changes to understory vegetation, insect prey availability, and roost tree abundance. High‐flying bats may be less influenced by fire‐induced changes to the understory because they forage above the forest canopy. Fire‐dependent forests are prevalent across the range of the endemic Florida bonneted bat (Eumops floridanus), a large, high‐flying, and critically endangered species, yet effects of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 59 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…39,40 ) and management of populations of rare and threatened species (e.g. 41,42 ) including the eastern regal fritillary. Study sites were managed with rotational burning during spring (March-May; hereafter spring fires) and late fall/winter (November-February; hereafter winter fires) according to a pre-determined fire rotation, with plans adjusted by vegetation growth, weather conditions, and fuel accumulation data.…”
Section: Methodsmentioning
confidence: 99%
“…39,40 ) and management of populations of rare and threatened species (e.g. 41,42 ) including the eastern regal fritillary. Study sites were managed with rotational burning during spring (March-May; hereafter spring fires) and late fall/winter (November-February; hereafter winter fires) according to a pre-determined fire rotation, with plans adjusted by vegetation growth, weather conditions, and fuel accumulation data.…”
Section: Methodsmentioning
confidence: 99%
“…The season in which the fire occurs may also influence how predators and prey respond to fire (e.g. Valentine et al ., 2007; Braun de Torrez, Ober & McCleery, 2018). For example, Conner, Castleberry & Derrick (2011) suggested that increased time between a fire event and green‐up may result in decreased prey survival due to the existence of a prolonged period of reduced food and shelter availability.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Also in northern Australia, ‘edge‐open’ foraging bats responded positively and negatively to low‐ and high‐severity burns, respectively, whereas bats that forage in the open showed a strong positive response to high‐severity burns (Broken‐Brow et al ., 2020). Similarly, in Florida, USA, bats increased their activity after wet season burns and even more so after dry season burns, likely because of increased availability of insect prey post‐fire (Braun de Torrez et al ., 2018). Tropical savanna bird abundance also increased after burning, with carnivore abundance highest after wet season burns, and insectivore and granivore abundance highest after dry season burns (Valentine et al ., 2007).…”
Section: How and Why Do Predators Respond To Fire?mentioning
confidence: 99%
“…Woody nesting substrates are often used in palustrine wetlands, and herbaceous nesting substrates are often used in lacustrine habitats (Fletcher et al, 2015). Vegetation succession and plant species patterns across the Everglades landscape are driven by a meshing of hydrology and fire (Lockwood et al, 2003), so it is likely that fire plays a role in habitat use for snail kites like it does for other Florida endangered species (e.g., the Cape Sable seaside sparrow, Ammospiza maritima mirabilis ; Benscoter et al, 2019 or the Florida bonneted bat, Eumops floridanus ; Braun de Torrez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%